From Aesop to Reynard beast literature in medieval Britain - Mann, Jill (Oxford University Press, 2009)
What do stories about animals have to tell us about human beings? This book analyzes the shrewd perceptions about human life - and especially human language - that emerge from narratives in which the main figures are 'talking animals'.